Satellite scientific data collection and accumulation system as a basis for cyber-physical systems construction - Hlukhov, Valerii; Lukenyuk, Adolf; Shenderuk, Sergii (Publishing House of Lviv Polytechnic National University, 2016)
The paper reviews technologies of computer systems the development of which has led to the emergence of cyber-physical systems – there are embedded computer systems, open systems interconnection model, multilayer computer systems, wireless communications, microelectromechanical systems, data protection technologies. It is noted that there are computer systems exist, whose parameters are close to those of cyber-physical systems ones, there are also groups of developers who have experience of in such systems designing. The satellite scientific data collection and accumulation system developed in Lviv Center of Institute for Space Research of NAS and SSA of Ukraine with the participation of Lviv Polytechnic National University Computers department is an example of such systems. In paper The main features of this system are described in the paper. The recommendations are given onf using it as the basis for the creation of advanced cyber-physical systems.
Keywords: cyber-physical system; scientific data collection and accumulation system; source packet; transfer frame; FPGA; SciWay